2020
DOI: 10.1108/ijsms-04-2019-0046
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the effects of outsourcing ticket sales force management

Abstract: PurposeThe purpose of the study is to ascertain whether sport organizations which outsource ticket sales force management outperform sports organizations which manage their ticket sales force internally, relative to ticket revenue and attendance.Design/methodology/approachThirteen years of ticket revenue and football attendance data were collected for National Collegiate Athletic Association (NCAA) Football bowl subdivision (FBS) Division I Athletics Departments (n = 126), as well as data on whether the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…While not surprising, such a result is alarming for sales managers, who, despite receiving hundreds of applicants for posted positions, are frequently unable to retain salespeople for much more than two years. Turnover is costly as evidenced by prior research suggesting ticket salespeople generate more revenue the longer they are employed (Popp et al, 2019b). Wakefield (2018) suggests an NBA ticket salesperson generates 3.4 times more revenue in their third year compared to their first and research in Major League Soccer found third-year salespeople outproduce first-year sellers 4 to 1 (Mickle, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While not surprising, such a result is alarming for sales managers, who, despite receiving hundreds of applicants for posted positions, are frequently unable to retain salespeople for much more than two years. Turnover is costly as evidenced by prior research suggesting ticket salespeople generate more revenue the longer they are employed (Popp et al, 2019b). Wakefield (2018) suggests an NBA ticket salesperson generates 3.4 times more revenue in their third year compared to their first and research in Major League Soccer found third-year salespeople outproduce first-year sellers 4 to 1 (Mickle, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding who leaves the salesforce, at what rate and for what reasons, are questions with which sales managers and researchers have wrestled for a long time. Attrition is an important concern for sales leaders because how quickly ticket salespeople leave their job affects organizational productivity and profitability (Bouchet et al, 2011;Mickle, 2010;Popp et al, 2019b;Wakefield, 2018). The significant costs in time and money to search, hire and train new salespeople is well documented in sales research (Darmon, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of studies have used fixed-effects models to the sport marketing context to investigate the impact on game attendance of star players, team performance or outsourcing ticket sales (DeSchriver, 2007; Popp et al , 2020; Shapiro et al , 2017; Spenner et al , 2010). Alexander and Kern (2004) modeled the relationship of market size, team performance and a new facility to franchise value and Paola and Scoppa (2012) designated team performance as the dependent variable in their utilization of a fixed-effects model to examination managerial turnover in Italian football.…”
Section: Methodsmentioning
confidence: 99%
“…IS outsourcing can be an efficient solution for implementing and maintaining IS programs, specifically for organizations that do not possess the staff, funds, or knowledge to manage IS efficiently (Cezar et al, 2016). Outsourcing has already established itself as an efficient way to manage support services, such as accounting and sales (Popp et al, 2020), customer support call centers (Ren & Zhou, 2008), and legal services (Lacity & Willcocks, 2013). Since the "Kodak experiment" in 1989, IT has also become a popular outsourced support service (Dibbern et al, 2004).…”
Section: Information Security Outsourcingmentioning
confidence: 99%